Automated fruit grading system - Wong, Kelvin Le Thai (2017)
In recent years, automatic visual inspection technology has become more potential and important to many areas. It is because the quality of fruits becoming an important factor for the consumer and is essential for marketing uniform high quality produce. The fruits grading factories have been set up to reduce production costs and improve fruit quality. Besides, an automatic visual inspection system aimed to replace the manual technique for grading of fruits as manual inspection faces problems in maintaining consistency and uniformity. This project describes the design of an automated fruit grading system. A prototype of the system is designed and tested. In this project, the detection of surface defect of fruits is described in details. The developed system starts the process by capturing the fruit's image using camera where the fruits are placed on a rotating desk. Then, the image is transmitted to the processing level where the grading is done using MATLAB. The fruits are graded based on their surface defects.